Serat dan Status Gizi Kaitannya dengan Tekanan Darah pada Pasien Hipertensi Rawat Inap di Rumah Sakit Umum Daerah Tugurejo Semarang - Fitria Nur Kholifah; Sufiati Bintanah; Erma Handarsari (Universitas Muhammadiyah Semarang, 2016)
Hypertension is called the silent killer is a disease prevalent in society is characterized by sistolic blood pressure ? 140 mmHg and diastolic ? 90 mm Hg. The fiber is called